Pengaruh suplementasi serat Psyllium husk dan diet rendah kalori seimbang terhadap berat badan, kadar kolesterol high-density lipoprotein, dan trigliserida serum pada obes I - Irnawaty Rasyid; Rachmad Soegih; Dante Saksono Harbuwono (Jurnal Gizi Klinik Indonesia, 2014)
Background: The increased prevalence of obesity will bring a great impact in the health sector, due to the effect of the influence of organ in the body such as type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Reduced energy diet and exercise are effective for management weight loss. During the restriction diet, an obese person should increase the amount of dietary fiber up to 20−35 g/day, specifically of soluble fiber, to more effective fat loss and improve serum high-density lipoprotein (HDL) and triglyceride (TG) cholesterol concentration. Psyllium husk (PH) is a source of natural soluble fiber obtained from Plantago ovate Forssk seed.Objective: The aim of the study have investigated the change of body weight, serum HDL cholesterol, and TG concentration in obese I after supplemented PH 8.4 g/day and balanced deficit calories diet (BDCD) for 4 weeks.Method: The survey used double-blind randomized clinical trial with parallel design. Subjects were randomly divided into two groups; treatment (T) group and placebo (P) group. The T subjects received psyllium husk (PH) 8.4 g/day and BDCD 1200 kcal/day and the P subjects received placebo and BDCD 1200 kcal/day. The analyzed used independent t-test and Mann-Whitney.Results: A total 28 subjects (14 subjects in each group) had completed the intervention. There were no serious adverse effects reported during the intervention. Intake of dietary fiber in T group was 17.2 ± 2.8 g/day had significantly higher than P group 8.6 (5.2−15.2) g/day, although supplemented with PH didn’t meet the recommendation of fiber intake (20-35 g/day). Decrease of body weight was -1,8 ± 0,8 kg and triglyceride level was -1,5 (-416−77) in T group that statistically insignificant difference (p=0,39 and p=0,84) with P group -1,6 ± 0,9 kg and -10,0 ± 31,3. Soluble supplementation (P group) increased serum HDL cholesterol concentration was 0,0 ± 4,3 mg/dL that statistically insignificant difference (p=0,86) with T group -0,4 ± 5,9.Conclusion: PH supplementation 8.4 g/day and BDCD 1200 kcal/day in obese I can not reduce body weight, serum high-density lipoprotein cholesterol, and triglyceride concentration level in 4 weeks.